Inflasi dan Suku Bunga Pada Harga Saham Perusahaan Yang Terdaftar di Bursa Efek Indonesia - Fifi Armelia; Lidya Martha (Transformasi: Journal of Economics and Business Management, 2023)
This study aims to examine the effect of inflation and interest rates on stock prices in companies listed on the Indonesia Stock Exchange in 2017-2021. The data used in this research is secondary data. The population in this study were 810 companies, the sampling procedure used a purposive sampling method based on predetermined criteria, so that a sample of 70 companies was obtained. The dependent variable in this study is stock prices, while the independent variables are inflation and interest rates. The data analysis method uses panel data. The results showed that inflation had a positive and insignificant effect on stock prices, interest rates had a negative and insignificant effect on stock prices.